Rufinamide, an antiepileptic drug, improves cognition and increases neurogenesis in the aged gerbil hippocampal dentate gyrus via increasing expressions of IGF-1, IGF-1R and p-CREB. (25th April 2018) - Chen, Bai Hui; Ahn, Ji Hyeon; Park, Joon Ha; Song, Minah; Kim, Hyunjung; Lee, Tae-Kyeong; Lee, Jae Chul; Kim, Young-Myeong; Hwang, In Koo; Kim, Dae Won; Lee, Choong-Hyun; Yan, Bing Chun; et al.
Abstract: Rufinamide is a novel antiepileptic drug and commonly used in the treatment of Lennox-Gastaut syndrome. In the present study, we investigated effects of rufinamide on cognitive function using passive avoidance test and neurogenesis in the hippocampal dentate gyrus using Ki-67 (a marker for cell proliferation), doublecortin (DCX, a marker for neuroblast) and BrdU/NeuN (markers for newly generated mature neurons) immunohistochemistry in aged gerbils. Aged gerbils (24-month old) were treated with 1 mg/kg and 3 mg/kg rufinamide for 4 weeks. Treatment with 3 mg/kg rufinamide, not 1 mg/kg rufinamide, significantly improved cognitive function and increased neurogenesis, showing that proliferating cells (Ki-67-immunoreactive cells), differentiating neuroblasts (DCX-immunoreactive neuroblasts) and mature neurons (BrdU/NeuN-immunoreactive cells) in the aged dentate gyrus compared with those in the control group. When we examined its mechanisms, rufinamide significantly increased immunoreactivities of insulin-like growth factor-1 (IGF-1), its receptor (IGF-1R), and phosphorylated cAMP response element binding protein ( p -CREB). However, rufinamide did not show any increase in immunoreactivities of brain-derived neurotrophic factor and its receptor. Therefore, our results indicate that rufinamide can improve cognitive function and increase neurogenesis in the hippocampus of the aged gerbil via increasing expressions of IGF-1, IGF-1R and p -CREB. Graphical abstract: Highlights: 4-week treatment of rufinamide (Ruf) increases short-term memory in the aged gerbil. Ruf increases neurogenesis in the aged hippocampal dentate gyrus (DG). Ruf treatment increases IGF-1, IGF-1R, and p -CREB in the aged DG. Ruf treatment does not affect expressions of BDNF and TrkB in the aged DG.